2000
DOI: 10.1006/viro.2000.0626
|View full text |Cite
|
Sign up to set email alerts
|

The Envelope Glycoprotein of Simian Immunodeficiency Virus Contains an Enterotoxin Domain

Abstract: By the use of a mouse model, the enteropathic effects of the simian immunodeficiency virus (SIV) surface unit (SU) envelope glycoprotein were explored. Purified SU (0.01-0.45 nmol) was administered intraperitoneally to 6- to 8-day-old mouse pups and induced a dose-dependent diarrheal response. Surgical introduction of SU into adult mouse intestinal loops revealed fluid accumulation without histological alterations and SU-treated unstripped intestinal mucosa induced chloride (Cl(-)) secretory currents in Ussing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Based on these data and on previous reports [in particular 6,8,10,35], we propose the following hypothesis for explaining the role of gp120 in the pathogenesis of HIV-1 enteropathy.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Based on these data and on previous reports [in particular 6,8,10,35], we propose the following hypothesis for explaining the role of gp120 in the pathogenesis of HIV-1 enteropathy.…”
Section: Discussionmentioning
confidence: 52%
“…Similar concentrations of SIV surface envelope glycoprotein (in the range of 75-300 nM) are needed to induce calcium or inositol triphosphate signals in HT-29 cells [35]. Swaggerty et al [35] observed that SIV surface envelope glycoprotein (0.02-0.45 nmol) induced a dose-dependent diarrhea in a mouse pup model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations